Robot adoption and urban total factor productivity: evidence from China - Li, Bowen; Zhou, Cai (Technological and Economic Development of Economy, 2024)
Industrial robots are having a profound and lasting impact on China’s economy. This research examines the deployment of industrial robots and their effects on urban total factor production from theoretical and empirical angles. It is created using panel data from 286 cities at the prefecture level between 2003 and 2017. It is found that: First, robot adoption promotes urban total factor productivity. Second, adopting robots has a more positive influence on urban total factor productivity development in western, underdeveloped, and less market-oriented areas compared to the developed and market-oriented areas in the east. Third, adopting robots could enhance urban innovation vitality, increase total factor productivity, boost industrial agglomeration, and improve technological progress or technical efficiency. Policy enlightenment provided by these findings can guide future technological advancements and promote high-quality city development.First published online 07 June 2024